Upaya Meningkatkan Keterampilan Membaca Pemahaman Siswa Sekolah Dasar Pada Pembelajaran Bahasa Indonesia Melalui Model Reading Guide - Rikmasari, Rima; Mujiani, Dwi Safitri; Aliza, Nurul (Bima Journal of Elementary Education, 2025)
This study aims to analyze the effectiveness of the Reading Guide model in improving reading comprehension skills among elementary school students in Indonesian language learning. The research background is based on the low level of students’ reading literacy, particularly in identifying main ideas, answering literal questions, making inferences, and drawing conclusions from texts. The study employed a quantitative approach with a quasi-experimental type using a one-group pretest–posttest design. The research subjects were 30 fourth-grade students of SD Islam Ummul Quro Bekasi, selected through purposive sampling. Data were collected using a reading comprehension test in the form of essay questions, which had been validated by experts and tested for reliability. Data analysis included descriptive statistics, N-Gain calculation, and a paired sample t-test. The results revealed a significant increase in the mean score from 55.3 on the pretest to 84.7 on the posttest, with a difference of 29.4 points. The N-Gain analysis indicated that 40.0% of the students were in the high category, 53.3% in the moderate category, and only 6.7% in the low category. The t-test results showed a significance value of 0.000 (p < 0.05), confirming a statistically significant difference between the pretest and posttest results. These findings emphasize that the application of the Reading Guide model is effective in improving elementary students’ reading comprehension skills. Therefore, this strategy can be recommended as a simple, practical, and impactful alternative to strengthening fundamental literacy skills.